Sikap Ibu Tentang Sex Educational Berhubungan dengan Pemberian Sex Educational pada Remaja Awal - Eva Sri Rahayu (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2020)
MOTHER'S ATTITUDE ABOUT SEX EDUCATION CONNECTED BY GIVING SEX EDUCATION IN EARLY ADOLESCENTS Abstract: Adolescence is a transitional period where in general it faces the same problem in understanding about sexuality, namely the lack of knowledge about sexuality and reproductive health which can be fatal. Knowledge about sexuality really needs to be possessed by adolescents, the current government program makes sexuality education approaches through morality approaches one of them through parents as part of the family. This study aims to analyze the relationship between knowledge and attitudes of parents with the provision of educational sex in early adolescents. This research is a quantitative study with a cross-sectional design approach. Research subjects were 88 mothers and 88 fathers who met the inclusion and exclusion criteria. Data collection through filling out questionnaires filled out by parents (mothers and fathers) of junior high school students. The results showed there was no correlation between mother's knowledge, father's knowledge and father's attitude about educational sex with the provision of educational sex in early adolescents, while for maternal attitudes had a correlation with the provision of educational sex in early adolescents with a p value of 0.001. The conclusion of this study is that the attitude of mothers who have a relationship with the provision of educational sex in early adolescents. Keywords: Knowledge, attitude, educational sex, adolescents Abstract: Masa remaja merupakan masa transisi dimana pada umumnya menghadapi permasalahan yang sama dalam memahami tentang seksualitas, yaitu minimnya pengetahuan tentang seksualitas dan kesehatan reproduksi yang dapat berakibat fatal. Pengetahuan tentang seksualitas sangat perlu dimiliki oleh remaja, program pemerintah saat ini membuat pendekatan pendidikan seksualitas melalui pendekatan moralitas salah satunya melalui orang tua sebagai bagian dari keluarga. Penelitian ini bertujuan untuk menganalisis hubungan antara pengetahuan dan sikap orang tua dengan pemberian sex educational pad remaja awal. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan desain Cross Sectional. Subjek penelitian berjumlah 88 orang ibu dan 88 orang ayah yang memenuhi kriteria inklusi dan ekslusi. Pengumpulan data melalui pengisian kuesioner yang di isi oleh orang tua (ibu dan ayah) dari siswa sekolah menengah pertama. Hasil penelitian menunjukan tidak ada korelasi antara pengetahuan ibu, pengetahuan ayah dan sikap ayah tentang sex educational dengan pemberian sex educational pada remaja awal, sementara untuk sikap ibu memiliki korelasi dengan pemberian sex educational pada remaja awal dengan nilai p 0,001. Kesimpulan dari penelitian ini bahwa sikap ibu yang memiliki hubungan dengan pemberian sex educational pada remaja awal. Kata Kunci : Pengetahuan, sikap, sex educational, remaja